DIPONEGORO AND THE ULAMA NUSANTARA NETWORK - Zainul Milal Bizawie (INC- Islam Nusantara Center, 2020)
The Javanese War was the event of the greatest resistance of the Javanese against the colonial authorities. As the last form of 'old order' resistance, the Java War witnessed the disarmament of the southern central Java palaces when their territories in eastern countries were finally annexed (1830-1831) (Houben 1994: 17-72). At the end of the war, Dutch control of Java was still unchallenged. Their role only ended 112 years later (1830-1942). That, too, was in the hands of the Japan (March 9, 1942), disputing only one day with the day when Diponegoro entered the city of Magelang to conduct a